2023
DOI: 10.1021/acsami.3c00714
|View full text |Cite
|
Sign up to set email alerts
|

Renal Clearable Quantum Dot–Drug Conjugates Modulate Labile Iron Species and Scavenge Free Radicals for Attenuating Chemotherapeutic Drug-Induced Acute Kidney Injury

Abstract: Chemotherapeutic drug-induced acute kidney injury (AKI) involves pathologically increased labile iron species in the kidneys that mediate the excessive generation of reactive oxygen species (ROS) to induce ferroptosis and apoptosis, subsequently driving renal dysfunction. Herein, we report renal clearable quantum dot−drug conjugates (QDCs) composed of carbon quantum dot (CDs), deferoxamine (DFO), and poly(ethylene glycol) (PEG) for attenuating chemotherapeutic drug-induced AKI. The CDs component in QDCs can no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…By constructing a quantum dot-drug conjugate compounded with carbon quantum dots, desferrioxamine, and polyethylene glycol, the researchers not only effectively scavenged excess intracellular Fe2+ and avoided the overproduction of ROS, but also had good efficacy in treating mice from CP-AKI. 88 , 89 Recent studies have found that dioscin can reduce the oxidative damage, apoptosis, and ferroptosis of the kidney through Nrf2/HO-1 signaling pathway, and play a protective role on CP-AKI. 90 Qi et al 91 found that CP-AKI was associated with an imbalance of ferritin metabolism in proximal tubular cells, and that administration of inositol promoted Hsc-70-interacting protein-mediated NOX4 ubiquitination, which effectively inhibited ferroptosis and improved CP-AKI.…”
Section: Ferroptosis and Nephrotoxic Drug-induced Akimentioning
confidence: 99%
“…By constructing a quantum dot-drug conjugate compounded with carbon quantum dots, desferrioxamine, and polyethylene glycol, the researchers not only effectively scavenged excess intracellular Fe2+ and avoided the overproduction of ROS, but also had good efficacy in treating mice from CP-AKI. 88 , 89 Recent studies have found that dioscin can reduce the oxidative damage, apoptosis, and ferroptosis of the kidney through Nrf2/HO-1 signaling pathway, and play a protective role on CP-AKI. 90 Qi et al 91 found that CP-AKI was associated with an imbalance of ferritin metabolism in proximal tubular cells, and that administration of inositol promoted Hsc-70-interacting protein-mediated NOX4 ubiquitination, which effectively inhibited ferroptosis and improved CP-AKI.…”
Section: Ferroptosis and Nephrotoxic Drug-induced Akimentioning
confidence: 99%
“…20–26 In addition, various antioxidant nanozymes have demonstrated promising effectiveness in the management of AKI. These nanozymes encompass metal complexes, 3,27–30 carbon dots, 31–33 and DNA origami. 34–37 Nanozymes offer significant advantages in enhancing bioavailability and exhibit significant potential in the therapeutic management of AKI.…”
Section: Introductionmentioning
confidence: 99%
“…22–25 Besides, ultrasmall nanocarbons with proper sizes and structures can exhibit prolonged body retention and kidney-targeting ability. 24,26,27 Inspired by the aforementioned characteristics, we envisioned that the integration of the pyroptosis inhibitory activity into nanocarbons may bring unexpected outcomes in AKI treatment. In this study, we present the design and construction of a pharmacologically active carbonized nanoinhibitor (P-RCDs) derived from a molecular pyroptosis inhibitor, 3,4′,5-trihydroxystilbene, for attenuating chemotherapeutic drug-induced AKI (Fig.…”
Section: Introductionmentioning
confidence: 99%